2020
DOI: 10.1186/s43046-020-00023-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic gastrectomy with D2 lymphadenectomy for gastric cancer: initial Egyptian experience at the National Cancer Institute

Abstract: Background: Laparoscopic gastrectomy has been used as a superior alternative to open gastrectomy for the treatment of early gastric cancer. However, the application of laparoscopic D2 lymphadenectomy remains controversial. This study aimed to evaluate the feasibility and outcomes of laparoscopic gastrectomy with D2 lymphadenectomy for gastric cancer. Results: Between May 2016 and May 2018, twenty-five consecutive patients with gastric cancer underwent laparoscopic D2 gastrectomy: eighteen patients (72%) underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
3
3
0
Order By: Relevance
“…In this study, the mean operating time was 295.5 minutes in the LSG arm and 272.5 minutes in the OSG group. These ndings are consistent with other studies, which have reported durations ranging from 196 to 370 minutes for LSG and 168 to 296 minutes for OSG [13], [21], [22]. Despite this difference, it is crucial to consider the non-signi cance of the operative time disparity and weigh it against the numerous bene ts offered by minimally invasive surgery.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In this study, the mean operating time was 295.5 minutes in the LSG arm and 272.5 minutes in the OSG group. These ndings are consistent with other studies, which have reported durations ranging from 196 to 370 minutes for LSG and 168 to 296 minutes for OSG [13], [21], [22]. Despite this difference, it is crucial to consider the non-signi cance of the operative time disparity and weigh it against the numerous bene ts offered by minimally invasive surgery.…”
Section: Discussionsupporting
confidence: 89%
“…Despite this difference, it is crucial to consider the non-signi cance of the operative time disparity and weigh it against the numerous bene ts offered by minimally invasive surgery. The mean blood loss of 207.5 ml in the LSG group was comparable to 202.5 ml in the OSG group and aligns with existing literature [13], [15], [17].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Meanwhile, the technology is limited when completion of lymph node dissection occurred. Although laparoscopic gastrectomy has been widely accepted as a treatment for early gastric cancer, the application of laparoscopic D2 lymphadenectomy remains controversial [ 6 ]. Recently, robotic systems have been developed [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%